SIGNIFICANCE OF ACQUIRED COLOR VISION DEFECTS IN THE DIAGNOSIS OF VASCULAR DISEASES - Erb, Carl; Weisser, Burkhard (Interdisciplinary Approaches to Medicine, 2024)
Color vision testing can be used to detect subtle disturbances in retinal function, which can often occur before clinical symptoms and, for the ophthalmologist, before visible changes in the fundus of the eye in general vascular diseases. This makes it possible to carry out rapid and inexpensive early diagnosis by detecting acquired color vision disorders, which can prevent further damage by optimizing therapy. Here it is particularly important to work closely with general practitioners and internists. Such aspects should be given greater consideration in occupational medicine. In many areas of industry, high demands are placed on color vision. In areas such as the textile industry, the chemical paint industry, the food industry, the automotive industry (paints) and in painting companies, normal color perception is of fundamental importance. Color vision testing is an inexpensive and easy-to-perform examination method that can provide an early indication of acquired color vision deficiency under standardized conditions. In addition to the detection of a generalized microcirculatory disorder, this determination is also useful in occupational medicine in order to better determine suitability for certain occupational groups. Keywords: color vision, vascular diseases, diabetes, arterial hypertension, migraine